2015
DOI: 10.1016/s1569-9056(15)60242-1
|View full text |Cite
|
Sign up to set email alerts
|

244 Discontinuation of dapoxetine treatment in patients with premature ejaculation: A 2-year prospective observational study

Abstract: Introduction: Although dapoxetine is the only oral pharmacologic agent approved for the treatment of premature ejaculation (PE) and is very effective, the discontinuation rate is high. Aim: To assess the discontinuation rate of patients with PE and the reasons for discontinuation in real-world practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This evidence revealed that behavioural therapy could extend the ejaculation latency and that combination therapy achieved better results than therapy without drug treatment. However, more RCTs are needed to evaluate the psychological treatment of PE (Abu & Abdelhamed, ; Cooper et al, ; Park, Park, & Moon, ). Studies have shown that approximately 30% of PE patients treated with paroxetine choose to discontinue the treatment after a relatively short time, and approximately 20% of people refuse to start medical treatment (Salonia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence revealed that behavioural therapy could extend the ejaculation latency and that combination therapy achieved better results than therapy without drug treatment. However, more RCTs are needed to evaluate the psychological treatment of PE (Abu & Abdelhamed, ; Cooper et al, ; Park, Park, & Moon, ). Studies have shown that approximately 30% of PE patients treated with paroxetine choose to discontinue the treatment after a relatively short time, and approximately 20% of people refuse to start medical treatment (Salonia et al, ).…”
Section: Discussionmentioning
confidence: 99%